Controllable growth of layered selenide and telluride heterostructures and superlattices using molecular beam epitaxy. Issue 7 (6th January 2016) - Vishwanath, Suresh; Liu, Xinyu; Rouvimov, Sergei; Basile, Leonardo; Lu, Ning; Azcatl, Angelica; Magno, Katrina; Wallace, Robert M.; Kim, Moon; Idrobo, Juan-Carlos; Furdyna, Jacek K.; Jena, Debdeep; et al.
Abstract: Abstract : Layered materials are an actively pursued area of research for realizing highly scaled technologies involving both traditional device structures as well as new physics. Lately, non-equilibrium growth of 2D materials using molecular beam epitaxy (MBE) is gathering traction in the scientific community and here we aim to highlight one of its strengths, growth of abrupt heterostructures, and superlattices (SLs). In this work we present several of the firsts: first growth of MoTe2 by MBE, MoSe2 on Bi2 Se3 SLs, transition metal dichalcogenide (TMD) SLs, and lateral junction between a quintuple atomic layer of Bi2 Te3 and a triple atomic layer of MoTe2 . Reflected high electron energy diffraction oscillations presented during the growth of TMD SLs strengthen our claim that ultrathin heterostructures with monolayer layer control is within reach.